O licenciamento ambiental como instrumento de um desenvolvimento verdadeiramente sustentável - Bezerra, Fabiano César Petrovich (2008)
Since the second half of the 20th century, mankind concerns about life quality and environment preservation began to grow. In Brazil, the edition of the Law nº 6.938/81, that instituted the National Policy of the Environment (Política Nacional do Meio Ambiente PNMA), contributing significantly to the singular treatment towards the environment by the Federal Constitution of 1988 (Constituição Federal de 1988), can be appointed as a landmark of this awareness. The Law nº 6.938/81, following the line observed on the legislation of some Brazilian States, predicted on its 9th article the instruments of PNMA, among which the environmental licensing can be highlighted. This instrument presents itself as indispensable to the construction, installation, extension and operation of enterprises and activities that utilize environmental resources, seen as effective and potentially polluter industries, or even to those that can cause environment degradation. On a parallel way and as a consequence of this awareness, the concept of development begins to acquire a new shape. The development of a country or a region begins to consider not only economical factors, but also environmental, political, cultural and social aspects. Ecodevelopment, or sustainable development, then, arises. In this way, through research on legislation and on theme related doctrine, this work has the intention of analyzing environmental licensing as a PNMA instrument responsible for uniting economical development and the right to an ecologically balanced environment, that is, by the consecution of a truly sustainable development